2019
DOI: 10.1186/s40623-019-1122-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations to explain the coseismic electromagnetic signals: a case study for a M5.4 aftershock of the 2016 Kumamoto earthquake

Abstract: Coseismic electromagnetic (EM) signals that appear from the P arrival were observed in a volcanic area during the 2016 Kumamoto earthquake. In this study, we conduct numerical simulations to explain the coseismic EM signals observed for a M5.4 aftershock of the earthquake. Initially, we adopt a water-saturated half-space model, and its simulation result for a receiver with a depth of 0.1 m suggests that the magnetic signals do not show up at the arrivals of P, refracted SV-P and Rayleigh waves because the evan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…Both theoretical and experimental studies have confirmed that the EK effect couples the seismic and EM fields (e.g., Garambois & Dietrich, 2002;Haartsen & Pride, 1997;Zhu et al, 1999). EK modeling techniques predict that an earthquake source can generate two kinds of EM signals, namely, the early and coseismic EM signals, and when applied to real earthquake events they can explain much of the observed data (Gao et al, 2016(Gao et al, , 2020Ren et al, 2014;Sun et al, 2019). For example, Gao et al (2016) simulated the coseismic EM data observed during the 2004 Parkfield M6 earthquake using a finite-fault model by the method of Hu and Gao (2011) and found that the simulated coseismic electric field matched the observed data in both amplitude and waveforms, showing the EK effect may explain the coseismic EM phenomenon.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Both theoretical and experimental studies have confirmed that the EK effect couples the seismic and EM fields (e.g., Garambois & Dietrich, 2002;Haartsen & Pride, 1997;Zhu et al, 1999). EK modeling techniques predict that an earthquake source can generate two kinds of EM signals, namely, the early and coseismic EM signals, and when applied to real earthquake events they can explain much of the observed data (Gao et al, 2016(Gao et al, , 2020Ren et al, 2014;Sun et al, 2019). For example, Gao et al (2016) simulated the coseismic EM data observed during the 2004 Parkfield M6 earthquake using a finite-fault model by the method of Hu and Gao (2011) and found that the simulated coseismic electric field matched the observed data in both amplitude and waveforms, showing the EK effect may explain the coseismic EM phenomenon.…”
mentioning
confidence: 91%
“…The EM signals measured during passage of seismic waves (hereafter referred to as coseismic EM signals) tend to be very similar to the corresponding seismic signals in waveform and frequency content (Gao et al., 2016; Matsushima et al., 2002; Sun et al., 2019; Tang et al., 2010). They may carry useful information about the subsurface material properties (Gao et al., 2016; Huang et al., 2015; Ren et al., 2016).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on numerical simulations, Ren et al (2016b) put forward the idea that evanescent seismoelectric waves could be the main contribution to coseismic EM signals. This idea was recently adopted to investigate actual coseismic EM signals associated with natural earthquakes (Dzieran et al, 2019;Sun et al, 2019).…”
mentioning
confidence: 99%